Harp Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
Harp syndrome, characterized by hypoprebetalipoproteinemia, acanthocytosis, retinitis pigmentosa, and pallidal degeneration, is described in three patients from the National Hospital, Queen Square, London, Newcastle General Hospital, and the Royal Free Hospital, London, UK.